Concordance to the correspondence of Voltaire - Besterman, T (Voltaire Foundation, 2017)
Preface I. Key to the contents of Voltaire's correspondence II. Key to the contents of Correspondence and related documents III. Concordance to the letters IV. Concordance to the appendixes V. Concordance to the supplements